The Essence of Technological Innovation and High-Tech and Offshore Entrepreneurship - a Study to Identify Possible Benefits from the Implementation of the Proposed Model Solution - Daniel KISAŁA; Milena BERA (Communications of International Proceedings, 2025)
Offshore wind energy, combines advanced technologies, significant capital investments and broad scientific and industrial cooperation with international market strategies. The aim of the article is to present to a wider audience how technological innovations and high-tech entrepreneurship can support the development of offshore wind energy. The article describes innovative gravity foundations as a promising and constantly developing high-tech technology for the wind sector. The recipients of the research are all future beneficiaries of the offshore energy market, for whom technological innovations can be an element of an international business strategy while taking into account the promoted policy of local content. The article evaluates the strengths and weaknesses of the proposed model, as well as the opportunities and threats associated with its implementation. Additionally, the actual implementation of model solutions was examined using company data and project documentation.
Keywords: high tech entrepreneurship; technological innovation; technology transfer wind power; economic development.